Erythrocytes, a New Contributor to Age‐Associated Loss of Blood–Brain Barrier Integrity (Adv. Sci. 20/2021). Issue 20 (21st October 2021) - Amiri, Payam; DeCastro, Jonalyn; Littig, Joshua; Lu, Hsiang‐Wei; Liu, Chao; Conboy, Irina; Aran, Kiana
Abstract : Blood–Brain Barriers In article number 2101912, Irina Conboy, Kiana Aran, and co‐workers show that erythrocytes derived from old mammals (mice and people) have deleterious effects on the integrity of the blood‐brain barrier, when compared to the young donor cells. This previously unknown change in erythrocyte behavior unveils a new mechanism of age‐associated neurological decline. Image credits: Ella Maru Studio.